“Workshop on Funding for Higher Education:A comparative analysis of Australia, India, Thailand, New Zealand and way Forward for Malaysia” - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
The National Higher Education Research Institute (IPPTN) in collaboration with the Ministry of Higher Education (MoHE) Malaysia coordinated a workshop on “Funding for Higher Education: A Comparative Analysis of Australia, India, Thailand,New Zealand and Way Forward for Malaysia ” on 29th - 30th of May 2007 which took place at Parkroyal Hotel, Kuala Lumpur. The programme attracted more than 20 participants from academics and researchers from local public and private universities, as well as policy makers from the Malaysian government’s fund arms for higher education students, National Higher Education Fund Corporation (PTPTN).